The sustainable development in international law and its relationship with climate change - Carnero Arroyo, Ena (2022)
The aim of this article is to study the relationship between the principle of sustainable development in international law and climate change. In the first place, the evolution of the  concept of sustainable development is analyzed through the study of the different United  Nations Conferences on Enviroment and Development (Earth Summits); as well as some  treaties that contain elements of the concept. This allows us to deduce that sustainable development has been incorporated as a principle in different areas of international law. Second, climate change is examined in light of the Climate Change Convention, the Kyoto Protocol, the  Paris Agreement and the SDGs, focusing on the principles related to sustainable development.